2018
DOI: 10.32604/biocell.2018.07009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between CD133, CK19 and G2/M in cirrhotic HCV (genotype-4) patients with or without accompanying tumor

Abstract: Hepatitis C virus (HCV)-cirrhotic patients have the highest threat of developing hepatocellular carcinoma (HCC) and may be at risk of extra hepatic cancer. The present study was designed to investigate CD133 and CK19 in HCV (genotype-4)-cirrhotic patients with/without HCC or extra hepatic cancer, to assess the degree of their correlation with cell cycle abnormalities and finally to assess the role of their combination as diagnostic tool for discrimination of cirrhotic patients with HCC from those with extra he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…As one of the conditions that can encourage lipid peroxidation diabetes is one of the pathologic conditions that might indirectly cause liver damage (El-Emshaty et al, 2018). In agreement with Al-Rawi (2007a) and Ene et al's (2007) studies, our present results revealed significant lowering in ALT and AST activities and a significant increase in blood albumin in diabetic animals administered with CQC when compared to the control untreated diabetic group.…”
Section: Discussionsupporting
confidence: 92%
“…As one of the conditions that can encourage lipid peroxidation diabetes is one of the pathologic conditions that might indirectly cause liver damage (El-Emshaty et al, 2018). In agreement with Al-Rawi (2007a) and Ene et al's (2007) studies, our present results revealed significant lowering in ALT and AST activities and a significant increase in blood albumin in diabetic animals administered with CQC when compared to the control untreated diabetic group.…”
Section: Discussionsupporting
confidence: 92%
“…The risk model-based screening strategy showed superior net benefit than screening all cirrhotic patients or screening none of the non-cirrhotics. There is an intensive effort to validate sensitive and specific HCC blood-based biomarkers[48,49]. Potentially, these markers may be efficient in early HCC detection and may stratify patients according to their HCC risk.…”
Section: Post-svr Hcc Surveillancementioning
confidence: 99%
“…Globally, endometrial cancer is the 6th utmost common cancer in females and the utmost common malignancy of the female genital area [25]. Predictive, diagnostic, and prognostic biomarkers were identified for several other cancers [26][27][28]. The present study was the A vital mechanism involved in tumorigenesis is the inhibition of apoptosis [29].…”
Section: Discussionmentioning
confidence: 60%